Experimental investigation of nucleate pool boiling heat transfer characteristics on modified copper surface via laser-structured microstructures - Sugumaran, Luvindran; Mohd Zubir, Mohd Nashrul; Kazi, Salim Newaz; Tuan Zahari, Tuan Zaharinie; Mt Aznam, Suazlan; Mohd Halil, Aiman (2023)
This study aims to evaluate the performance of boiling heat transfer on a structured surface subjected to constant heat flux. A nanosecond laser ablation was used to create different surface profiles on copper samples. Specifically, a series of step-like microstructured surfaces with varying secondary groove widths were fabricated to investigate their effect on nucleate pool boiling heat transfer performance of distilled water. The results indicated a significant enhancement in heat transfer performance for the laser structured surfaces compared to the smooth surface at low heat flux. This improvement was attributed to the increased nucleation frequency, surface area, and nucleation site density. However, at higher heat flux, the surface with a smaller secondary groove width (LS 2) exhibited a decline in heat transfer performance, which was likely due to larger bubble escaping resistance. In contrast, the surface with a larger secondary groove width (LS 1) demonstrated the best heat transfer performance. The current work would help in finding an optimum surface structuring design for gaining higher boiling heat transfer performance which benefits industries dealing with thermal management processes.